2016
DOI: 10.1080/00325481.2017.1264854
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of high frequency chest wall oscillation and intrapulmonary percussive ventilation for airway clearance in pediatric patients with tracheostomy

Abstract: This study suggests that airway clearance by IPV therapy could be more effective and beneficial in providing airway clearance in specific subsets of the medically complex pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…IPV could play an important role in the prevention of these pulmonary complications in this population. Both Bidiwala et al and Reardon et al showed beneficial effects in most outcome measures over specific periods of time (1 y and 7 m, respectively). Fewer hospitalizations and a reduction in the use of respiratory drugs when treated regularly with IPV compared to standard physiotherapy were key findings in both articles.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…IPV could play an important role in the prevention of these pulmonary complications in this population. Both Bidiwala et al and Reardon et al showed beneficial effects in most outcome measures over specific periods of time (1 y and 7 m, respectively). Fewer hospitalizations and a reduction in the use of respiratory drugs when treated regularly with IPV compared to standard physiotherapy were key findings in both articles.…”
Section: Discussionmentioning
confidence: 91%
“…The study by Van Ginderdeuren et al was the only one with a very high score with a result of nine out of 10. Four studies scored high on the overall score with a result of 7 or 6 out of 10, two scored moderate with a score of 4 or 5, and two studies scored low with a result of 3 out of 10 . These last two studies did not compare results with another group or control period, resulting in a lower overall score, because criteria involving blinding, randomization, and comparison between groups could not be scored .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations